2013
DOI: 10.1016/j.jaac.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Conduct Disorder and Initiation of Substance Use: A Prospective Longitudinal Study

Abstract: Objective To examine the influence of conduct disorder (CD) on substance initiation. Method Community adolescents without CD (n= 1165, mean baseline age= 14.6), with CD (n= 194, mean baseline age= 15.3), and youth with CD recruited from treatment (n=268, mean baseline age= 15.7) were prospectively followed and re-interviewed during young adulthood (mean ages at follow-up respectively: 20, 20.8, and 24). Young adult retrospective reports of age of substance initiation for 10 substance classes were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 32 publications
2
28
1
Order By: Relevance
“…It would appear that from these two sets of results, variables that are typically good predictors of levels of substance use do not discriminate strongly between early and later initiators of inhalants. This seems to be in conflict with prior studies that find higher risk for physiologic, behavioral, and psychological problems among early initiators (Brouette & Anton, 2001; Hopfer et al, 2013; Howard et al, 2010). Two factors may help explain this apparent contradiction.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…It would appear that from these two sets of results, variables that are typically good predictors of levels of substance use do not discriminate strongly between early and later initiators of inhalants. This seems to be in conflict with prior studies that find higher risk for physiologic, behavioral, and psychological problems among early initiators (Brouette & Anton, 2001; Hopfer et al, 2013; Howard et al, 2010). Two factors may help explain this apparent contradiction.…”
Section: Discussioncontrasting
confidence: 83%
“…Furthermore, this difficult distinction is true both for American Indian and White youth. Given the association of early inhalant initiation with many negative outcomes (Brouette & Anton, 2001; Hopfer et al, 2013; Howard et al, 2010), it would be reasonable to suspect that key risk factors would help differentiate these two groups. But the current results do not support this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 Early environmental factors that predict CD at ages 14 to 16 include low SES, childhood adversity, parental substance use disorder (SUD), negative home environment, and delinquent peers. 7 American Indian (AI) and other Indigenous youth are disproportionately exposed to these poverty- and family adversity-related risks, 8 in large part due to current and historical factors (e.g., forced relocation, boarding schools, social marginalization), and thus may be particularly at risk for CD and related negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Among adolescents whose externalizing behavior problems are severe enough to merit entry into substance use disorder treatment, very high prevalence of CD is generally seen (Dennis et al, 2004), with more than 80% of such youths having CD in some studies (Sakai, Hall, Mikulich-Gilbertson and Crowley, 2004). While a good deal of work has characterized SUD youths with CD in terms of their longitudinal course and associated co-morbid disorders (e.g., Crowley and Riggs, 1995; Walters, 2014; Hopfer et al, 2013), recent findings have suggested that CD is a relatively heterogeneous phenotype and that CD youth might be meaningfully divided based on callous-unemotional traits (e.g., Frick and White, 2008). After reviewing evidence showing that callous-unemotional traits are measurable in childhood (Frick and Ellis, 1999), stable (Frick and White, 2008), and predict worse outcomes (Frick and White, 2008; Frick, Cornell, Barry, Bodin and Dane, 2003; Frick and Dickens, 2006), the Diagnostic and Statistical Manual of Mental Disorders' (DSM-5) ADHD and Disruptive Behavior Disorders Work Group developed and described methods for categorical identification of callous-unemotional traits (Frick and Moffitt, 2012) and included a “limited prosocial emotions” (LPE) specifier for the CD diagnosis in DSM-5 (APA, 2013).…”
Section: Introductionmentioning
confidence: 99%